Pengaruh Dompet Digital dan Variasi Produk Terhadap Keputusan Pembelian di Shopee - Henriawan, Desan; Puspasari, Dewi (Universitas Koperasi Indonesia, 2023)
Online shopping transactions experience a change in habits towards using digital wallets. The fast-paced era demands effectiveness and efficiency from almost all aspects. In addition, it is necessary to pay attention to the variety of products offered by online marketplaces, considering that many competitors continue to fight over consumer purchasing decisions. This research method uses quantitative survey research with digital wallet variables, product variations and purchasing decisions. The research location is located around the city of Bandung. Data analysis using regression testing on variables. The results of digital wallet research and product variations have a significant simultaneous effect on purchasing decisions. Furthermore, digital wallets have an effect on purchasing decisions but product variations were found to have no effect on purchasing decisions.